2014
DOI: 10.1002/cphc.201402262
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Alkaline Stability of Imidazolium Cations by Substitution

Abstract: Imidazolium cations are promising candidates for preparing anion-exchange membranes because of their good alkaline stability. Substitution of imidazolium cations is an efficient way to improve their alkaline stability. By combining density functional theory calculations with experimental results, it is found that the LUMO energy correlates with the alkaline stability of imidazolium cations. The results indicate that alkyl groups are the most suitable substituents for the N3 position of imidazolium cations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 39 publications
(58 reference statements)
2
46
0
Order By: Relevance
“…With respect to alkaline stability, in addition to S N 2 and deprotonation degradation mechanisms, imidazolium-based head groups can also be degraded via a ring opening mechanism ( Fig. 3e) [67,68]. Multiple literature sources have reported that the electron-deficient C2 position of imidazolium-based head groups is highly susceptible to nucleophile attack, which could be mitigated through the addition of large functional groups to sterically hinder OHattack [67,69,70].…”
Section: Synthesis Of Anion Exchange Membranesmentioning
confidence: 99%
“…With respect to alkaline stability, in addition to S N 2 and deprotonation degradation mechanisms, imidazolium-based head groups can also be degraded via a ring opening mechanism ( Fig. 3e) [67,68]. Multiple literature sources have reported that the electron-deficient C2 position of imidazolium-based head groups is highly susceptible to nucleophile attack, which could be mitigated through the addition of large functional groups to sterically hinder OHattack [67,69,70].…”
Section: Synthesis Of Anion Exchange Membranesmentioning
confidence: 99%
“…The spin‐unrestricted generalised gradient approximation proposed by Becke, Lee, Yang, and Parr (GGA‐BLYP) was used as the exchange‐correlation functional together with a double numerical basis set with polarisation (DNP) for all calculations . The convergence criteria for geometry optimisations were set to fine quality (ie, self‐consistent field (SCF) threshold value of 1×10 −6 , convergence tolerance energy of 1×10 −5 Ha, and maximum force and displacement of 2×10 −3 Ha/Å and 5×10 −3 Å, respectively) . The direct inversion in the iterative subspace value of 6 and a smearing value of 5×10 −3 Ha were also used to accelerate convergence of SCF iterations .…”
Section: Methodsmentioning
confidence: 99%
“…The use of water as an implicit solvent was implemented utilising a conductor‐like screening model (COSMO), wherein the solvent is represented as a homogeneous dielectric medium (ε water = 78.54). The transition state (TS) search was performed using the complete linear synchronous transit/quadratic synchronous transit method . Vibrational frequencies were calculated to ensure that the initial structures are in their lowest energy state and the TSs have only one imaginary frequency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations